Pengaruh Penekanan Anggaran dan Motivasi Terhadap Hubungan Antara Partisipasi Anggaran Dengan Senjangan Anggaran Serta Dampaknya Pada Kinerja Manajerial (Studi Pada Yayasan Pendidikan dan Koperasi Propinsi Banten) - Karsam Karsam (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
There is a budgetary slack in the budget formulation ofthe Educational Foundation and Cooperative in Banten Province. This situation is because of the assesment standard of managerial performance that is based on the achievement of budget targets, where the ownersapply the standard of the budget by doing the emphasis budgets, as well as their adverse selection. It will make the managers and other people know more about the situation and the prospects of the institution, it is also because of the moral hazard when the actions of managers is unknown by the shareholders or owners of the company. The data were collected by questionnaires which were answered by 93 respondents who got involved as the team in budgeting form each organizations and analysed by using the path analysis with partial least square (PLS). The results of data analysis showed that the influence of budget emphasis level on the relationship between participative budgeting and budgetary slack is 30.1%. Meanwhile 69.9% is influenced by other variables that were not used in this study. Improving the effectiveness of the budget should be done by the management through giving the authority, evaluate and ensure that the budgeting team has considered the emphasis the budget comprehensively,measure the managerial performance in determines the planning and budgeting.Pengaruh Penekanan Anggaran dan Motivasi Terhadap Hubungan Antara Partisipasi Anggaran Dengan Senjangan Anggaran Serta Dampaknya Pada Kinerja Manajerial (Studi Pada Yayasan Pendidikan dan Koperasi Propinsi Banten)